2014
DOI: 10.1038/emm.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous deletion of floxed genes mediated by CaMKIIα-Cre in the brain and in male germ cells: application to conditional and conventional disruption of Goα

Abstract: The Cre/LoxP system is a well-established approach to spatially and temporally control genetic inactivation. The calcium/calmodulin-dependent protein kinase II alpha subunit (CaMKIIα) promoter limits expression to specific regions of the forebrain and thus has been utilized for the brain-specific inactivation of the genes. Here, we show that CaMKIIα-Cre can be utilized for simultaneous inactivation of genes in the adult brain and in male germ cells. Double transgenic Rosa26+/stop-lacZ::CaMKIIα-Cre+/Cre mice ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(45 reference statements)
2
21
0
Order By: Relevance
“…First is that Foxn1, and constructs regulated by this locus, joins an expanding list of genes expressed in tissues where they were not generally expected, often including the male germline, see [9,1012] for examples. Expression of Foxn1[Cre] in the male germline can be a useful attribute, since it facilitates generation of knockout sperm in males heterozygous for genes that are lethal when homozygous.…”
Section: Discussionmentioning
confidence: 99%
“…First is that Foxn1, and constructs regulated by this locus, joins an expanding list of genes expressed in tissues where they were not generally expected, often including the male germline, see [9,1012] for examples. Expression of Foxn1[Cre] in the male germline can be a useful attribute, since it facilitates generation of knockout sperm in males heterozygous for genes that are lethal when homozygous.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the Camk2a-cre lines they used can induce a simultaneous deletion of floxed Htt gene in the brain and male germ cells (Choi et al, 2014), the possibility that the sterility they observed could be due to an impaired hypothalamic-pituitary-testis axis caused by the Cre-mediated recombination in the brain could not be excluded. In this study, we generated a CKO mouse that had conditional knockout of Htt specifically in the male germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results hint that Htt might play an essential role during spermatogenesis in testis. However, considering that the Camk2a-cre lines they employed can induce a simultaneous deletion of floxed Htt gene in the brain and male germ cells (Choi et al, 2014), it is necessary to generate a germ-cell-conditional knockout mouse (CKO) model to directly confirm the possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Cre transgene in the testis was also reported in other Camk2α-Cre transgenic mouse lines and the recombination efficiency in the testis differed depending on floxed genes. 24…”
Section: Generation Of Constitutive and Neuronspecific Crls1 Knockomentioning
confidence: 99%